Answers

2014-11-25T18:14:09+08:00
2x + 5y = 5    ----equation 1
-3x + 5y = 5   ----equation 2
------------------
Subtract equation 2 from equation 1
     2x + 5y = 5
-  -3x + 5y = 5
     5x + 0 = 0
      5x = 0
        x = 0
-----------------
Substitute x=0 to equation 1
2x + 5y = 5
2(0) + 5y = 5
            5y = 5
              y = 1
-----------------
Therefore the two lines intersect at (0,1)
--------------------
For the graph, let's consider the x and y intercepts of the two lines
LINE 1: 2x + 5y = 5
x-intercept, y=0
               2x + 5(0) = 5 
               2x = 5
                 x = 5/2
            x-intercept (5/2,0)
y-intercept, x=0
              2(0) + 5y = 5
               5y = 5
                 y = 1
             y-intercept (0,1)
---------------------
LINE 2: -3x + 5y = 5
x-intercept, y=0
              -3x + 5(0) = 5
              -3x = 5
                x = -5/3
             x-intercept (-5/3,0)
y-intercept, x=0
              -3(0) + 5y = 5
               5y = 5
                 y = 1
             y-intercept (0,1)
--------------------------
see attachment for the graph 
0